INTEGRASI MODERASI BERAGAMA DALAM PEMBELAJARAN IPS MI: KAJIAN EMPERIS DAN PETA MATERI UNTUK PGMI - Nurul Yakin (CV. Jendela Gagasan, 2025)
Religious moderation has become a strategic agenda in primary education in Indonesia, including at the Madrasah Ibtidaiyah (MI) level. This article aims to examine patterns of understanding religious moderation in educational literature, identify effective integration strategies in social studies (IPS) instruction at MI, and develop a curriculum map of religious moderation materials relevant for the Madrasah Ibtidaiyah Teacher Education Program (PGMI). The study employs a qualitative approach based on field research at MI Miftahul Ulum Desa Jarin Kabupaten Pamekasan. The findings indicate that religious moderation is understood as values of balance, tolerance, and social justice, which align with the characteristics of IPS. Effective integration strategies are implemented through contextual, thematic, and reflective approaches. This article contributes to strengthening the pedagogical framework of PGMI in fostering moderate and inclusive IPS learning.